Versatile Synthesis of Amphiphilic Oligo(Aliphatic-Glycerol) Layer-Block Dendrons with Different Hydrophilic-Lipophilic Balance Values - Choi, Lai-Sheung; Chow, Hak-Fun (Synlett, 2013)
A series of amphiphilic oligo(glycerol-aliphatic) layer-blocked dendrons with different hydrophilic-lipophilic balance values (3.5–15.0) was prepared for use in controlled drug delivery and self-assembly studies. The synthetic strategies involved first a convergent growth of the inner hydrophobic sector followed by a divergent growth of the outer hydrophilic sector.
Keywords: dendrimers; dihydroxylation; Mitsunobu reaction